Deep anterior lamellar keratoplasty following thermokeratoplasty assisted epikeratophkia: A novel two-stage one-graft method to treat acute corneal hydrops - Liu, Chunyu; Huang, Xinyu; Shen, Jiaqi; Zhang, Yushan; Zhang, Li; Bi, Yanlong (Frontiers in Medicine, 2023)
Purpose: To evaluate the clinical effects of deep anterior lamellar keratoplasty (DALK) using a single graft after thermokeratoplasty assisted epikeratophakia for the treatment of acute corneal hydrops. Methods: This novel surgical procedure was performed on seven eyes of seven patients between 2019 and 2020. The procedure combines a first-stage surgery of thermokeratoplasty assisted epikeratophkia with intracameral sterile air injection and a second-stage surgery of DALK using the same corneal graft for both procedures. Main outcome measures included pre- and postoperative corrected distance visual acuity (CDVA) and anterior segment optical coherence tomography (AS-OCT) parameters. Corneal transparency, epithelization, and the presence of neovascularization were evaluated at the 1-year follow-up visit. Results: Corneal edema resolved rapidly in six of the seven cases. The mean central corneal thickness was significantly reduced from baseline to 1 day, 1 week, 1 month, and 2 months after the first-stage surgery (P < 0.0001). At a mean of 2.1±0.7 months after the first-stage surgery, DALK was successfully performed in all cases. Six months later, the mean central corneal thickness was 611±31 μm and the mean thickness of the recipient’s residual stroma bed was 20±6 μm at the central corneal area. Mean LogMAR CDVA improved from 1.74±0.34 at baseline to 0.20±0.11 after DALK (P < 0.0001). No postoperative complications appeared in our case series during the one-year observation period. Conclusion: Very good visual results were obtained with a novel technique (thermokeratoplasty assisted epikeratophakia followed by DALK using the same corneal graft) in the treatment of acute corneal hydrops.